EVIDENCE OF AN ABNORMAL INTRAMUSCULAR COMPONENT OF FATIGUE IN MULTIPLE SCLEROSIS - SHARMA, KHEMA R. (1995)
The goals of this study were to investigate muscle fatigue in patients with multiple sclerosis (MS), and to determine the relationships between muscle fatigue, clinical status, and perceived fatigue. The fatigability of the anterior tibial muscle was quantitated in patients and controls during 9 min of intermittent stimulation (used to eliminate central sources of muscle fatigue). During exercise, the decline in tetanic force, phosphocreatine, and intracellular pH was greater in patients than in controls. The compound muscle action potential amplitude did not decrease during exercise, indicating that there was no failure of neuromuscular transmission during fatigue. Thus, the excessive fatigue in MS developed from sources beyond the muscle memberane. Following exercise, the recovery of tetanic force was delayed in patients (a pattern that suggests abnormal excitation-contraction coupling), whereas the recovery of metabolites was complete in both groups. Muscular fatigue was correlated with clinical disability but not with perceived fatigue. These results suggests that fatigue in MS has both central (perception, upper motor neuron dysfunction) and peripheral (impaired metabolism and excitation-contraction coupling) components.